Elucidating the unknown transcriptional responses and PHR1-mediated biotic and abiotic stress tolerance during phosphorus limitation. (11th January 2023) - Scheible, Wolf-Rűdiger; Pant, Pooja; Pant, Bikram D; Krom, Nick; Allen, Randy D; Mysore, Kirankumar S
Abstract: Phosphorus (P) limitation in the majority of world soils is a major constraint for plant growth and crop productivity. RNA sequencing was used to discover novel P-responsive gene transcripts (PRGTs) in leaves and roots of Arabidopsis. Hisat StringTie and the Cufflinks TopHat transcript assembler were used to analyze reads and identify 1074 PRGTs with a >5-fold altered abundance during P limitation. Interestingly, 60% of these transcripts were not previously reported. Among the novel PRGTs, 106 were from unannotated genes, and some were among the most P-responsive, including At2g36727 which encodes a novel miRNA. Annotated novel PRGTs encode transcription factors, miRNAs, small signaling peptides, long non-coding RNAs, defense-related proteins, and transporters, along with proteins involved in many biological processes. We identified several genes that undergo alternative splicing during P limitation, including a novel miR399- resistant splice variant of PHOSPHATE2 ( PHO2.2 ). Several novel P-responsive genes were regulated by PHOSPHATE STARVATION RESPONSE1 ( PHR1 ), PHR1-LIKE 1 ( PHL1 ), and PHO2 . We discovered that P-limited plants show increased resistance to pathogens and drought stress mediated by PHR1–PHL1. Identification of novel P-responsive transcripts and the discovery of the influence of P limitation on biotic and abiotic stress adds a significant component to our understanding of plant P signaling. Abstract : Phosphorus limitation elicits the expression of several novel genes including many previously unannotated genes, non-coding RNAs, small peptides, and alternatively spliced RNAs, and leads to enhanced disease and drought tolerance.